Synthesis and Characterization of Banana Frond-Nanocytosan Bioadsorbent - Desika Devani Surbakti; Herlinawati (Universitas Negeri Medan, 2025)
FTIR characterization of the activated carbon showed the presence of functional groups including –OH (3207 cm⁻¹), aliphatic C–H (2886–2837 cm⁻¹), C≡C or CO₂ (2352–2120 cm⁻¹), aromatic C=C (1592 cm⁻¹), C–O (1086 cm⁻¹), and metal–O (533 and 465 cm⁻¹). The FTIR spectrum of chitosan indicated the presence of –OH and –NH groups (3641 cm⁻¹), –COO⁻ (1411 cm⁻¹), and glucose ring structures (870 and 711 cm the optimum result was achieved with 1% nanochitosan-coated adsorbent at a mass of 2,5 g and a contact time of 30 minutes, resulting in an FFA reduction of 2.51%. The nanochitosan-coated activated carbon showed the highest adsorption efficiency at 73.74%.